Religious Experience in the Hindu Tradition - McDaniel, June (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
This Special Issue of Religions brings together a talented group of international scholars who have studied and written on the Hindu tradition. The topic of religious experience is much debated in the field of Religious Studies, and here, we present studies of the Hindu religious experience explored from a variety of regions and perspectives. Our intention is to show that the religious experience has long been an important part of Hinduism, and should not be dismissed or considered as irrelevant. As a body of scholarship, these articles refine our understanding of the range and variety of religious experience in Hinduism. In addition to their substantive contributions, the authors also show important new directions in the study of the third-largest religion in the world, with over one billion followers.